tDCS stimulation segregates words in the brain: evidence from aphasia - Fiori, Valentina; Cipollari, Susanna; Di Paola, Margherita; Razzano, Carmelina; Caltagirone, Carlo; Marangolo, Paola (Frontiers in Human Neuroscience, 2013)
A number of studies have already shown that modulating cortical activity by means of transcranial direct current stimulation (tDCS) improves noun or verb naming in aphasic patients. However, it is not yet clear whether these effects are equally obtained through stimulation over the frontal or the temporal regions. In the present study, the same group of aphasic subjects participated in two randomized double-blind experiments involving two intensive language treatments for their noun and verb retrieval difficulties. During each training, each subject was treated with tDCS (20 min., 1mA) over the left hemisphere in three different conditions: anodic tDCS over the temporal areas, anodic tDCS over the frontal areas and sham stimulation, while they performed a noun and an action naming tasks. Each experimental condition was run in five consecutive daily sessions over three weeks with 6 days of intersession interval. The order of administration of the two language trainings was randomly assigned to all patients. Overall, with respect to the other two conditions, results showed a significant greater improvement in noun naming after stimulation over the temporal region, while verb naming recovered significantly better after stimulation of the frontal region. These improvements persisted at one month after the end of each treatment suggesting a long-term effect on recovery of the patients’ noun and verb difficulties. These data clearly suggest that the mechanisms of recovery for naming can be segregated coupling tDCS with an intensive language training.